EDUKASI TUMBUHAN BERKHASIAT ANTI DIABETES DARI BAHAN BAKU IE BU PEUDAH SEBAGAI KEARIFAN LOKAL MASYARAKAT DESA GAMPONG BARO, IDI CUT - ACEH TIMUR - Mastura; Sarah Niaci; Marsihat Sukiwono Silitonga; Dahliana; Elisa Agustin (Fakultas Teknik, Universitas Samudra, 2023)
Indonesia is a country located in the equatorial region and has a tropical climate, so Indonesia grows lots of plants. In particular, Aceh has many plants which are used as traditional medicine, for example eating Ie Bu Peudah which is a typical Acehnese food whose basic ingredients are made from various kinds of leaves and spices that have been dried for approximately three days at room temperature. Ie Peudah is made with grown using a mortar and then sifted using a 100-mesh sieve until it forms like flour. Based on research, the leaves made into Ie Bu Peudah contain secondary metabolites including Alkaloids, Steroids, Terpenoids, Saponins, Flavonoids, and Phenols. So Ie Bu Peudah is very suitable for degenerative sufferers. Degenerative diseases are non-communicable diseases that become chronic due to exacerbations. Decreased function of body organs due to the aging process, such as heart disease, hypertension, diabetes, and obesity.